Analysis of outcomes in patients with ST-segment elevation myocardial infarction aged 90 years and older: a single center experience - P. D. Duplyakova; T. V. Pavlova; D. V. Duplyakov (Российский кардиологический журнал)
Aim. To evaluate the effectiveness and safety of an invasive approach in patients with ST-segment elevation myocardial infarction (STEMI) aged 90 years and older.Material and methods. This retrospective single-center study was conducted at the V. P. Polyakov Samara Regional Clinical Cardiology Dispensary. In 20132020, 104 patients aged 90 years and older were hospitalized with a diagnosis of STEMI. The mean age of patients was 91,7 years (90-100), while the proportion of women was 67,3%. Patients included in the analysis were divided into groups of conservative treatment (n=81, mean age, 91,9 (90-100) years, women 70,4%) and invasive management (coronary angiography + percutaneous coronary intervention (PCI)) (n=23, mean age, 91,0 (90-94) years, women, 56,5%).Results. The groups were comparable in basic characteristics. In-hospital mortality in the conservative strategy group was 48,1% vs 17,4% in the invasive management group (p=0,009; odds ratio (OR) 3,35; 95% confidence interval (CI) 1,23-9,15). During the first year after discharge, 25,9% (n=21) died in the conservative strategy group and 30,4% (n=7) in the invasive strategy group (p=0,79; OR 0,85; 95% CI 0,42-1,75). In total (during the hospitalization period and within 1 year after discharge), 60 people (74,1%) died in the conservative strategy group, while in the invasive treatment group — 11 (47,8%) (p=0,02; OR 3,11; 95% CI 1,19-8,11). Life expectancy in patients with STEMI aged 90 years and older after discharge from hospital was 83,95 days for the conservative strategy group and 103,85 days for the invasive strategy group (p=0,67).Conclusion. The data obtained in our study support primary PCI as a treatment strategy for patients with STEMI aged 90 years and older.